Algal biochar enhances the re-vegetation of stockpiled mine soils with native grass. (15th September 2015) - Roberts, David A.; Cole, Andrew J.; Paul, Nicholas A.; de Nys, Rocky
Abstract: In most countries the mining industry is required to rehabilitate disturbed land with native vegetation. A typical approach is to stockpile soils during mining and then use this soil to recreate landforms after mining. Soil that has been stockpiled for an extended period typically contains little or no organic matter and nutrient, making soil rehabilitation a slow and difficult process. Here, we take freshwater macroalgae ( Oedogonium ) cultivated in waste water at a coal-fired power station and use it as a feedstock for the production of biochar, then use this biochar to enhance the rehabilitation of two types of stockpiled soil – a ferrosol and a sodosol – from the adjacent coal mine. While the biomass had relatively high concentrations of some metals, due to its cultivation in waste water, the resulting biochar did not leach metals into the pore water of soil-biochar mixtures. The biochar did, however, contribute essential trace elements (particularly K) to soil pore water. The biochar had very strong positive effects on the establishment and growth of a native plant (Kangaroo grass, Themeda australis ) in both of the soils. The addition of the algal biochar to both soils at 10 t ha −1 reduced the time to germination by the grass and increased the growth and production of plant biomass. Somewhat surprisingly, there was no beneficial effect of a higher application rate (25 t ha −1 ) of the biochar in the ferrosol, which highlights the importance of matching biochar application rates to the requirements of different types of soil. Nevertheless, we demonstrate that algal biochar can be produced from biomass cultivated in waste water and used at low application rates to improve the rehabilitation of a variety of soils typical of coal mines. This novel process links biomass production in waste water to end use of the biomass in land rehabilitation, simultaneously addressing two environmental issues associated with coal-mining and processing. Highlights: Coal mines must revegetate land post lease but this often has limited success. We produce biochar from macroalgae grown in waste water at a power station. We use the biochar to aid the revegetation of two soils from an adjacent coal mine. The biochar improved the germination and growth of a native grass in the two soils. Macroalgae can treat waste water, recycle CO2 and assist mine revegetation.